Assessment of Sadawarna Dam to Support Environmentally Sustainable Development - Setiawan, Rizki Bangun; Suharyanto, Suharyanto; Sukamta, Sukamta; Asad, Mohammad Bagus Wiratama (Universitas Tribhuwana Tunggadewi Malang, 2025)
Sadawarna Dam, one of Indonesia's national strategic projects, located in the Cipunegara River Basin, plays a crucial role in ensuring food security, controlling floods, and providing a raw water supply. Community activities around the reservoir have the potential to degrade water quality, making continuous monitoring necessary. This study evaluates the water quality condition of Sadawarna Dam through analysis of physical, chemical, and biological parameters using the Pollution Index method (Minister of Environment Decree No. 115 of 2003) in the upstream, reservoir, and downstream areas, providing a comprehensive overview of pollution levels and their relevance to environmentally sustainable principles. Measurement results show that, based on Class I Water Quality Standards, the Pollution Index (PI) values range from 3.61 to 5.20. In comparison, based on Class II Standards, the PI values range from 3.54 to 5.11. These values indicate that water quality in the reservoir and downstream areas falls into the